Reassessing Patient Satisfaction: Social Determinants and Hospital Quality in Indonesia - Sudirman, Sudirman; Yani, Ahmad; Andri, Mohamad (YCAB Publisher, 2025)
Background: Patient satisfaction is widely recognized as a crucial indicator of healthcare quality, shaped not only by clinical outcomes but also by social determinants of health such as education, economic stability, neighborhood environment, and social/community context. Objectives: This study aimed to identify the key social determinants influencing patient satisfaction at Undata General Hospital, Palu, Indonesia, assess the strength of associations between these determinants and satisfaction outcomes, and highlight practical implications for improving patient-centered care in resource-constrained hospital settings. By focusing on social determinants, the research addresses existing gaps in understanding how contextual and relational factors contribute to hospital service quality. Methods: A quantitative, cross-sectional design was employed between January and March 2025, with 97 patients recruited through proportionate stratified sampling across wards. Data were collected using structured questionnaires and analyzed with chi-square tests to examine associations between social determinants and patient satisfaction. Results: The findings revealed that education and economic stability, while descriptively linked to differences in satisfaction, were not statistically significant predictors. In contrast, neighborhood environment and social/community context showed strong and significant associations with patient satisfaction. Patients who perceived the hospital environment as clean, safe, and comfortable were markedly more satisfied, while those embedded in supportive social networks also reported higher satisfaction. These results align with global evidence that highlights environmental quality and social cohesion as decisive determinants of patient experience, particularly in resource-limited contexts. The discussion emphasized how expectation theory and cultural competence frameworks explain the observed patterns, reinforcing the importance of aligning care with both structural and social dimensions. Conclusion: In conclusion, this study contributes to the growing body of literature on patient satisfaction by demonstrating that environmental and community factors outweigh individual socioeconomic attributes in shaping perceptions of care. The findings highlight practical implications for hospital managers and policymakers, suggesting that investments in environmental improvements and community engagement strategies are crucial pathways to enhance patient-centered quality care in Indonesia and similar settings.